THE MEN WHO ARE LOST IN TIME: ALIENATION IN MATT HAIG'S HOW TO STOP TIME (2017) - Rifki Gustian Romdon, - (2019)
Postmodern condition, marked by the advancement of the globalization of media, technology, and economy, raises a sense of discontent in the society. Detachment, isolation and alienation are examples of how the development affects human's sociological and psychological state. This study attempts to propose the idea of alienation as a significant issue and is still relevant in society nowadays by presenting examples found in the novel How to Stop Time (2017) by Matt Haig. The examples found are reflected upon theories and condition in the contemporary society. As for the framework of alienation, this study employs the three aspects of alienation proposed by Jaeggi (2014) namely the intertwined powerlessness and meaninglessness, the construct of social heteronomy, and the relation of relationlessness, to unravel how it is depicted in the novel through the relation and interrelation among the main character's experiences, his associates, other characters, and the time itself. The result of the study suggests that the novel depicts all the aspects of alienation proposed by Jaeggi (2014). The quasi-immortal trait of the main character and his associates, also show other issues which dominantly are the issue of loneliness and the loss of freedom through their experience of alienation. The findings in the study suggest that the theory is productive and proposes a practical contrasting stand point of alienation which is the relation of appropriation. Further research on the novel How to Stop Time (2017) is suggested due to its rich potential of explorability.